Intelligent and Cognitive Technologies in Education of International Economic Relations Students and Human Resource Development: Methodology in Language Teaching and Distance Learning - Yuriy Dyachenko, Nayden Nenkov; Galyna Bondarenko, Mariana Petrova; Pustovit, Valeriia (European Journal of Sustainable Development, 2017)
This study is aimed at ensuring quality education and promoting lifelong learning opportunities we need for empowering learning. This paper attempts to consider the possibility and unite the conditions for intelligent and cognitive technologies application to human resource development and education of students. There is proposed Actor-Network Theory as a theoretical framework for managing actors of educational process as human and non-human agent interactions. As a core of interactions we use Facebook social infrastructure which is a tool to build the global community. We consider artificial technologies and distance learning in education, cognitive technologies for human resource development, especially for internally displaced persons in Ukraine. As a hub for this technologies we use chatbot based on natural language processing wit.ai technologies. Intelligent and cognitive technologies provide the opportunities to incorporate cognitive characteristics of each student with a view to address individual approach for students. We developed the curriculum “International economic relations” based on relevant stakeholders' requests with regard to intelligent and cognitive technologies. In future it can yield the most suitable solution for knowledge transfer from one agent to another in order to ensure inclusive and equitable quality education. Keywords: Intelligent and Cognitive Technologies, Human Resource Development, International Economic Relations, Methodology in Language Teaching